Competence view and its implications for clusters analysis in turbulent environment - Janiszewski, Adam (Lviv Polytechnic Publishing House, 2016)
In the paper Author tries to consider two of main reasons for inter-organizational cooperation and their relation to some specific environment. Clusters are chosen with regard to their accumulated knowledge resources and other unique characteristics which make them so much different when compared to hierarchical structures. To analyze possible impacts of this specific kind of environment on shaping the motives for inter-organizational collaboration Author refers to typology of districts based on selected dimensions which was once created to satisfy a need to resolve much of an ambiguity of existing research on industrial districts. Finally, research proposition is developed.
Keywords: clusters; inter-organizational relations